Filsafat Kristen dan Paradigma Inklusif di Era Modern: Kritik Terhadap Pengaruh Tren Budaya - Suarman Mezuari Waruwu; Mozes Lawalata (Jurnal Budi Pekerti Agama Kristen dan Katolik, 2024)
Presents a critique of the influence of cultural trends on Christian philosophy and the inclusive paradigm in the modern era. This article seeks to criticize the influence of cultural trends on Christian philosophy and the inclusive paradigm in modern times. By identifying and analyzing the implications of cultural trends in these two concepts, the author aims to gain a deeper understanding of how values ​​and beliefs in contemporary society are influenced and change in line with the development of cultural trends. The method used in this research is qualitative research methods. with a literature study approach. First of all, the study will begin with a comprehensive literature review, aiming to gather the latest information regarding the development of Christian philosophy, inclusive paradigms, and cultural trends in the context of modern times. The next step is to conduct an in-depth conceptual analysis, taking into account relevant theological, philosophical and socio-cultural perspectives. Modern cultural trends have brought about significant changes in the way humans interact, think and communicate. In the context of the inclusive paradigm, this change has several implications. Advances in information technology and digital culture have made individual needs more diverse and complex. An inclusive paradigm must be able to capture and meet these needs contextually. Inclusive education, for example, should focus on developing individuals' abilities to adapt to change and interact with various cultures. the influence of cultural trends on Christian philosophy and inclusive paradigms in the modern era, with a focus on their impact in the context of morality, biblical authority, and inclusivity. Through conceptual analysis and critique of the implications of cultural trends, this article highlights challenges and opportunities for Christian philosophy and inclusive paradigms.